Pelvic and breast examination skills curricula in United States medical schools: a survey of obstetrics and gynecology clerkship directors. Issue 1 (December 2016) - Dugoff, Lorraine; Pradhan, Archana; Casey, Petra; Dalrymple, John; Abbott, Jodi; Buery-Joyner, Samantha; Chuang, Alice; Cullimore, Amie; Forstein, David; Hampton, Brittany; Kaczmarczyk, Joseph; Katz, Nadine; et al.
Abstract Background Learning to perform pelvic and breast examinations produces anxiety for many medical students. Clerkship directors have long sought strategies to help students become comfortable with the sensitive nature of these examinations. Incorporating standardized patients, simulation and gynecologic teaching associates (GTAs) are approaches gaining widespread use. However, there is a paucity of literature guiding optimal approach and timing. Our primary objective was to survey obstetrics and gynecology (Ob/Gyn) clerkship directors regarding timing and methods for teaching and assessment of pelvic and breast examination skills in United States medical school curricula, and to assess clerkship director satisfaction with current educational strategies at their institutions. Methods Ob/Gyn clerkship directors from all 135 Liaison Committee on Medical Education accredited allopathic United States medical schools were invited to complete an anonymous 15-item web-based questionnaire. Results The response rate was 70%. Pelvic and breast examinations are most commonly taught during the second and third years of medical school. Pelvic examinations are primarily taught during the Ob/Gyn and Family Medicine (FM) clerkships, while breast examinations are taught during the Ob/Gyn, Surgery and FM clerkships. GTAs teach pelvic and breast examinations at 72 and 65% of schools, respectively. Over 60% of schools use some type of simulation to teach examination skills. Direct observation by Ob/Gyn faculty is used to evaluate pelvic exam skills at 87% of schools and breast exam skills at 80% of schools. Only 40% of Ob/Gyn clerkship directors rated pelvic examination training as excellent, while 18% rated breast examination training as excellent. Conclusions Pelvic and breast examinations are most commonly taught during the Ob/Gyn clerkship using GTAs, simulation trainers and clinical patients, and are assessed by direct faculty observation during the Ob/Gyn clerkship. While the majority of Ob/Gyn clerkship directors were not highly satisfied with either pelvic or breast examination training programs, they were less likely to describe their breast examination training programs as excellent as compared to pelvic examination training—overall suggesting an opportunity for improvement. The survey results will be useful in identifying future challenges in teaching such skills in a cost-effective manner.